2018
DOI: 10.1080/00015385.2018.1478266
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin as a novel marker; well correlated with mortality and morbidity in patients with advanced systolic heart failure

Abstract: Neopterin is a biomarker reflecting ongoing inflammatory process in deteriorating heart. High level of serum neopterin concentrations was associated with mortality and morbidity in systolic HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Demir et al demonstrated that neopterin is a powerful marker of inflammation in patients with HF. Thus, it can be used in the diagnosis of HF [ 23 ]. Moreover, they found that within 1-year follow-up, patients with high morbidity and mortality had higher levels of neopterin concentrations as compared to patients without risk of morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Demir et al demonstrated that neopterin is a powerful marker of inflammation in patients with HF. Thus, it can be used in the diagnosis of HF [ 23 ]. Moreover, they found that within 1-year follow-up, patients with high morbidity and mortality had higher levels of neopterin concentrations as compared to patients without risk of morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that within 1-year follow-up, patients with high morbidity and mortality had higher levels of neopterin concentrations as compared to patients without risk of morbidity or mortality. One-year follow-up hospitalisation also correlated well with neopterin serum levels making it a valuable marker for disease prognosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors found a correlation between elevation of urine Neopterin levels and cardiac structural and functional abnormalities evaluated by echocardiography in those patients (Shao et al 2014). Demir et al evaluated in a prospective study the connection between serum neopterin levels and morbidity and mortality due to HF (Demir et al 2019). Average neopterin serum concentration was significantly higher in the HF group compared to the control (Demir et al 2019).…”
Section: Neopterin In Congestive Heart Failurementioning
confidence: 99%
“…К биологическим маркерам воспаления, привлекающим внимание исследователей, относится неоптерин (НП), являющийся неспецифическим и высокочувствительным фактором активации моноцитарного звена клеточного иммунитета и усиленной выработки активных субстанций кислорода при различных патологических состояниях [8].…”
unclassified